Comparison between HSP70 Levels in Acute and Chronic Coronary Artery Diseases - Wurood A.Kadhim1, Noora M.Kareem2, Samar A. Al-Shami3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Heat shock proteins are a family of endogenous proteins that act as molecular chaperon and increase in different stress situations like heart disease and atherosclerosis. Therefore, the aim of this study was to investigate whether there is a difference between Hsp70 level in the blood of myocardial infarction patients and apparently normal population; and between recent myocardial infarction patients and previous myocardial patients using immunocytochemistry technique. Method: Peripheral blood sample was taken from 50 patients with history of myocardial infarction divided into two groups (11 with acute or recent myocardial infarction and 39 with old or chronic myocardial infarction. Another 50 apparently healthy individuals were taken as a control group. Heat shock protein 70 level was measured by immunocytochemistry technique. Results: There was significant rise of heat shock protein 70 in myocardial infarction patients as compared with control group. Also, a significant decrease in heat shock protein 70 level in the chronic myocardial infarction patients group as compared with the acute myocardial infarction patients group. Conclusion: this study showed that heat shock protein 70 increases in acute myocardial infarction patients’ but its level decreases in chronic myocardial infarction. So heat shock protein 70 can be used as a biomarker to differentiate acute, from chronic, myocardial infarction and may be helpful as an indicator of acute myocardial infarction.